Kant e la Rivoluzione Francese: liberali e/o reazionari fra passione e storia - Bianchini, Sara (2019)
The article comes from an attempt to find a connection, within a part of Kantian philosophy, among the three terms of “passion”, “history” and “Revolution” (especially French). The fundamental interest is to answer the following questions:what role do passions have in the rise of history? And what significance has been the French Revolution representing in the course of human affairs? The research was mainly concerned with the commentary of some of the nine theses of the Kantian text Idea of a universal history from the cosmopolitan point of view but also based on other texts of the philosopher of Könisberg, such as The Faculty conflict and The metaphysical principles of the doctrine of the Laws. It has been structured around the following points: the role of sociable insociability in giving birth to society and therefore history, the role of the people in determining history, the Kantian position in favour and then against the French Revolution. Trying to determine if we can maintain a line of substantial continuity, despite the differences, in the Kantian thought on the French Revolution expressed in the above texts, the article also questions the relationship between the progress of reason in the search for knowledge and moral growth, and philosophy of history (particularly thinking about the comparison between the idea of “purpose” of history and the use of reason, a comparison mediated by the concept of “organization”).